THE ENTREPRENEURIAL ECOSYSTEM AS A DETERMINANT OF ENTREPRENEURIAL MINDSET AND CORPORATE PERFORMANCE IN THE WESTERN STATES OF NIGERIA - Godspower Akpoyibo (Program Magister Administrasi Publik, 2026)
The study investigates the interplay between entrepreneurial ecosystems, entrepreneurial mindset, and enterprise pe4formance among SMEs in Western Nigeria. Hinged on entrepreneurial ecosystem theory and entrepreneurial mindset frameworks, the study explore both direct and indirect effect pathways through which ecosystem factors shape enterprise-level results. Applying a quantitative research design, relevant data were gathered from 224 SMEs decision makers using a structured and validated questionnaire. Descriptive and inferential statistical analyses, including regression modeling were conducted to test three hypotheses: the effect of entrepreneurial ecosystems on entrepreneurial mindset, the influence of entrepreneurial mindset on enterprise performance, and the direct effect of entrepreneurial ecosystems on enterprise. The findings indicate that entrepreneurial ecosystems significantly enhance entrepreneurial mindset (β = 0.3443, t = 5.47, p < 0.001), which, in turn, positively affects enterprise performance (β = 0.3883, t = 4.04, p < 0.001). More so, entrepreneurial ecosystems exert statistically and direct influence enterprise performance (β = 0.3864, t = 3.90, p < 0.001). Together these outcomes demonstrate a dual mechanism whereby well-designed ecosystems not only provide tangible resources and institutional backing but equally shape cognitive orientations that drive SME growth, market expansion, and profitability. The study advances theoretical understanding by empirically validating the linkages between ecosystem dynamics, entrepreneurial cognition, and firm performance, while offering practical guidance for policymakers, development agencies, and SME leaders operating in resource-constrained contexts.